2007
DOI: 10.1038/nphys564
|View full text |Cite
|
Sign up to set email alerts
|

Conditional statistics of electron transport in interacting nanoscale conductors

Abstract: There is an intimate connection between the acquisition of information and how this information changes the remaining uncertainty in the system. This trade-off between information and uncertainty plays a central role in the context of detection. Recent advances in the ability to make accurate, on-chip measurements of individual-electron current through a quantum dot 1-8 (QD) have been enabled by exploiting the sensitivity of a second current, passing through a nearby quantum point contact (QPC), to the fluctua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
137
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 30 publications
1
137
0
2
Order By: Relevance
“…In our case, the current in the most interesting regime is proportional to t 2 x, where x is exponentially small in ⌬ / k B T. Since the tunneling amplitude t can, in principle, be made arbitrarily small, sequential tunneling becomes the dominant process. Recently, it was shown that noise spectroscopy deep inside the Coulomb-blockade regime is possible [23][24][25][26] and in agreement with the sequential-tunneling description.…”
Section: Model and Theoretical Methodsmentioning
confidence: 64%
“…In our case, the current in the most interesting regime is proportional to t 2 x, where x is exponentially small in ⌬ / k B T. Since the tunneling amplitude t can, in principle, be made arbitrarily small, sequential tunneling becomes the dominant process. Recently, it was shown that noise spectroscopy deep inside the Coulomb-blockade regime is possible [23][24][25][26] and in agreement with the sequential-tunneling description.…”
Section: Model and Theoretical Methodsmentioning
confidence: 64%
“…2(a)]. For example, in quantum dot circuits in the Coulomb-blockade regime the dots act as the sites and the electrodes as the particle reservoirs [24,[32][33][34][35]. Driven by thermal fluctuations, particles make random transitions either between the system and the reservoirs or from one site to another.…”
Section: Modelmentioning
confidence: 99%
“…In these systems, the low (kilo-hertz) tunneling rates allow for detection of individual electrons in real-time using a nearby quantum point contact whose conductance is sensitive to the charge occupations of the dots. 3,5,6 Although quantum effects are typically suppressed at the long time scales characterizing the charge transport, quantum dots provide a unique setting to experimentally test theoretical predictions for high-order statistics. Remarkably, time-dependent cumulants of the transferred charge beyond the 15th order have recently been measured in single-electron transport through a Coulomb blockade quantum dot [7][8][9] and a wealth of statistical data is now available.…”
Section: Introductionmentioning
confidence: 99%